Tunicate-associated bacteria show a great potential for the discovery of antimicrobial compounds - Ayuningrum, Diah; Liu, Yang; Riyanti; Sibero, Mada T.; Kristiana, Rhesi; Asagabaldan, Meezan A.; Wuisan, Zerlina G.; Trianto, Agus; Radjasa, Ocky Karna; Sabdono, Agus; Schäberle, Till F.; Justus Liebig University Giessen (My University, 2019)
Tunicates (Ascidians, sea squirts) are marine protochordates, which live sedentary or sessile in colonial or solitary forms. These invertebrates have to protect themselves against predators and invaders. A most successful strategy, to not being eaten by predators and prevent pathogenic microorganisms to settle, is the usage of chemical molecules for defence. To accomplish this, tunicates take advantage of the specialized metabolites produced by the bacteria associated with them. Therefore, the microbiome of the tunicates can be regarded as a promising bioresource for bacterial strains producing compounds with antibacterial activity. The aim of this study was to test this hypothesis by (i) isolation of tunicate-associated bacteria, (ii) analysis of the antibacterial activities of these strains, and (iii) purification and structure elucidation of an active compound derived from this bioresource. In total, 435 bacterial strains were isolated and thereof 71 (16%) showed antibacterial activity against multidrug resistant (MDR) bacteria. Therefrom, the ethyl acetate crude extracts from liquid fermentations of 25 strains showed activity against MDR Extended-Spectrum Beta-Lactamase (MDR-ESBL) Escherichia coli, MDR Bacillus cereus, Micrococcus luteus, and Bacillus megaterium. Phenotypic analysis based on 16S rDNA sequencing revealed the active strains belonging to different genera and phyla, like Bacillus, Pantoea, Pseudoalteromonas, Salinicola, Streptomyces, Vibrio and Virgibacillus. To obtain first insights into the molecules responsible for the antibacterial activities observed, strain Pseudoalteromonas rubra TKJD 22 was selected for large-scale fermentation and the active compound was isolated. This allowed the purification and structure elucidation of isatin, a compound known for its strong biological effects, thereunder inhibition of Gram-positive and Gram-negative pathogens.
Keywords: ddc:630